The 22nd And 25th Amendments: Constitutional Succession And Presidential Term Limits - Badawi, Habib (Universitas Jambi, Fakultas Hukum, 2026)
This study examines the constitutional tension between the 22nd and 25th Amendments to the United States Constitution, analyzing how their structural interaction creates pathways through which presidential term limits may be circumvented through non-electoral succession mechanisms. Integrating constitutional institutionalism, democratic consolidation theory, and power distribution theory, the study conducts a comparative analysis of the two amendments' divergent constitutional grammars—the 22nd Amendment's prohibition on being